Product diversification and internationalization of Mexican companies - Galván Vera, Antonio; García Fernández, Francisco; Delgado Rivas, Jesús Gerardo (Cuadernos de Administración, 2021)
This article was prepared to provide evidence as to whether Mexican companies that diversify their products are more likely to internationalize their business units. The study concentrated on Mexican companies that list on the Mexican Stock Exchange, so that evidence could be found regarding the propensity of said firms to have multi-segment activities and to sell in foreign markets. The companies that were studied had representative market shares. The methodology was quantitative and descriptive, and used variables such as sales, net income, and total assets to establish the companies’ patterns of behaviour. Companies seek to diversify in order to grow, to put new products on the market, to enter new markets, and to seek new challenges. Diversification has costs and associated risks, but can also enable a company to maximize profits. The authors’ analysis goes further, to show which companies diversify in Mexico’s emerging economy, and which ones also have a presence in international markets. The majority of Mexican companies that opt to diversify and operate internationally face challenges such as the distinct, associated costs that are due to the companies’ inexperience in foreign markets, as well as to the institutional restrictions in emerging markets. However, some results indicate that over time, as the companies gain understanding and experience, they become able to take advantage of the benefits of a greater international diversification.